Does Information Technology Contribute to Improving the Quality of Education? Empirical Analysis from Saudi Arabia - Elimam, Haga; Alattas, Halah; Ashkan, Jude; Ahmed, Naema (European Journal of Sustainable Development, 2025)
The most significant visible innovation in this globalization period has been Information and Communication Technology (ICT). It has transformed the world into a global village with limitless connectivity, interactive organizations, knowledge exchange, and worldwide access. It is both a cross-cutting concern and a necessary tool for social and economic progress. For decades, ICT has played a vital role in job creation, job skill development, and manufacturing. Adopting ICT may significantly reduce a society’s corruption, resulting in a forward-thinking government in the country. Many individuals’ lives and livelihoods, particularly those in rural regions, cannot be enhanced without utilizing the ICT scope. However, a developing country like Saudi Arabia, with enormous potential, is still distant from adopting ICT, despite numerous challenges, when the entire globe is developing with the blessings of ICT. The present study has presented a complete empirical examination of information and communication in developing nations, focusing on Saudi Arabia. This study applied econometric analysis to examine the role of ICT in improving the quality of education in Saudi Arabia for the period 1990-2022. This study employed a vector error correction model (VECM) approach for empirical estimation. This study concluded that ICT contributed significantly to improving the education index in Saudi Arabia. It is recommended that policymakers of developing countries divert their attention towards ICT-related investment to enhance the level of education index. Keywords: Developing Nation, Education, Information and Communication Technology, Quality of Education.